Analisis Faktor â€“ Faktor yang Mempengaruhi Remaja Putri terhadap Perilaku Kekerasan dalam Pacaran di SMA â€œXâ€ Kota Semarang - Anantri, Khansa Maulidta (Jurnal Kesehatan Masyarakat (e-Journal), 2015)
Women National Comission recorded that there are 21% violence behavior in dating with 61 victims.BP3AKB Central Java recorded 12 violence victims in dating is occured in high school.High number of violent behavior in dating is came from knowledge and attitude to violence behavior in dating that is not realized and understood by teenager.Female students of X High School in Semarang who experience violence in dating are 48.2%.The purpose of this research is to analyze the relation between knowledge and attitude of teenage girl to violence behavior in dating in X secondary school in Semarang.This research is using quantitative method with cross sectional approach.The population is active student (female) in X secondary school in Semarang with total amount 592 people and 85 samples who are choosen by random sampling method with sample taking technic is propportional random sampling.The source of this data is using primary and secondary data.The data analysis is using univariate and bivariate with Chi Square statistical test (significance level 0.05).Most of the respondents were 17-20 years of age (late teens) (63.5%) and grade level respondents were in grade 10 (35, 7%). Respondents have less knowledge category (62.4%), the attitude of the respondents in both categories (56.5%), infrastructure (56.5%), family support (61.2%), the support of friends both categories (52, 9%) and support teachers (58.8%).The result of Chi Square test found there is relation between age, grade levels, attitudes, infrastructure, family support, and the support of friends as for the knowledge and support of the teachers are not relate to violent behavior in dating inX high school in Semarang.